ANALISIS TERHADAP PENDAMPINGAN DIFABEL TUNANETRA DI PANTI KARYA HEPHATA HKBP LAGUBOTI TAHUN 2017 - Desein B. Hutasoi (Areopagus : Jurnal Pendidikan Dan Teologi Kristen, 2018)
Abstract, This research aims to describe dan analyze the accompaniment which have done to blindness disabled. This research uses qualitative research type. The process of collecting data is done through interview. As for interviews conducted, aims to know things as follows: 1. How is the accompaniment done to the blindness disabled in creation house Hephata HKBP Laguboti 2. Whether creation house Hephata HKBP Laguboti has applied to the paradigm of the incarnation of Jesus Christ. The data source obtained in this research comes from 8 informants with different functional tasks, namely the leader, head of the dormitory, spiritual section, companion, and the blind person with disabilities. The results of the analysis indicate that the mentoring applied to the blindness disabled has applied mentoring with the incarnation perspective of Jesus Christ, which they call by the term inherent, meaning that the companion positioned himself to live and be with the disabled by living in one house and doing activities together. But, according to the researchers, the accompaniment with the incarnate perspective of Jesus Christ has not been fully applied. This can be seen from the duties and responsibilities of the companion that focuses on the function of supervising and caring for the disabled and the criteria that must be possessed by the companion is discipline and determination to serve as Jesus did the duties as shepherd.